A 1 × 2 triple‐band printed antenna array for use in next generation flying AD‐HOC networks (FANETs). Issue 3 (March 2016) - Khawaja, Bilal A.; Tarar, Munir A.; Tauqeer, Tauseef; Amir, Faisal; Mustaqim, Muhammad
ABSTRACT: A triple‐band 1 x 2 microstrip patch antenna array is proposed for use in next generation flying ad‐hoc network (FANET) communication in multi‐UAV systems. The antenna array resonates in the 3.6 GHz, 5.2 GHz and 6.7 GHz frequency bands, respectively. The antenna was designed and simulated using Agilent ADS Momentum using FR4 epoxy glass substrate ( εr  = 4.2 and h  = 1.66mm). A hybrid feed technique is used for antenna arrays with quarter‐wave transformer based network to match the impedance from the feed‐point to the antenna to 50Ω. The antenna is optimized to resonate at triple‐bands by introducing two symmetrical slits at the non‐radiating edges of the patch. The bandwidths achieved for the three bands are 130 MHz, 125 MHz and 180 MHz, respectively, which are very practical. The antenna array design is less complex and can be used for the advanced antenna beam‐steering systems in next generation FANETs. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:606–611, 2016